Assessing the Need for Lean Methodology Training and Institutional Commitment in Emergency Medical Dispatch: Implications for Efficiency and Project Management - Kawther El Aifa (18464449) (2024)
Background Lean methodology, originally pioneered in the automotive sector, has successfully enhanced efficiency by eliminating waste and boosting profitability. Although its implementation within the healthcare sector is relatively nascent, it holds significant promises. This study aimed to investigate the applicability and implications of the Lean approach within the Emergency Medical Dispatch (EMD) environment at Hamad Medical Corporation Ambulance Service (HMCAS) in Qatar. Methods A qualitative analysis was conducted employing semi-structured interviews targeted at leaders and management within the Communications division of HMCAS. Thematic analysis using inductive coding was executed using the NVivo 12 software. Results A total of 12 staff members in leadership roles were interviewed. While the interviewees exhibited strong leadership skills, two key gaps were identified: firstly, a “limited understanding of Lean methodology in healthcare” and the potential value-added to the EMD environment, and secondly, a “deficiency in project management knowledge”. Additional sub-themes were identified and are presented in Table 1 according to the role of the interviewees. Conclusion The findings indicate a need for enhanced education on Lean methodology within this setting. Adopting Lean could significantly improve project management competencies and, consequently, the success rate of projects within the EMD context. This could contribute to better patient outcomes and more effective and streamlined operations. These improved competencies could considerably raise the success rates of various projects undertaken within the EMD context. Moreover, the benefits are multi-dimensional; they extend beyond operational efficiencies potentially positively impacting patient outcomes. Effective project management can lead to a more efficient utilization of resources, thereby expediting patient care processes and contributing to improved patient well-being. Therefore, these findings strongly advocate for an institutional commitment towards Lean training and its integration into the standard operating procedures for leaders, thereby catalyzing achieving healthcare excellence.